Serangan Siber Sebagai Penggunaan Kekuatan Bersenjata dalam Perspektif Hukum Keamanan Nasional Indonesia (Cyber Attacks as the Use of Force in the Perspective of Indonesia National Security Law) - Diny Luthfah (Fakultas Hukum Universitas Trisakti, 2021)
Cyber Attack is part of use of force. The scope of use of cyber force in this article is limited to use by state against another state. The increasing of cyber attack grow within the awareness of every country in the world including Indonesia in matters of strategy and regulated their National Security Law. Interpreted cyber attack as some forms of offensive attacks will be challenging. The reason why will be difficult to regulate is that the factual bases for there have to be casualties, physical destruction and attribution will be addressed. Furthermore Indonesia needs to develop new policy and regulated cyber attack in Indonesia National Security Law.